Pengaruh Komposisi Katalis pada Pembuatan Komposit Sebagai Aplikasi untuk Body Kontes Mobil Hemat Energi (KMHE) - Hamid, Abdul; Ali Zainal Abidin, Muhammad; Annafiyah, Annafiyah; Dayi Febriana, Ike; Miftahatul Ilmah, Aurista; Abdullah, Mohammad (Indonesian Society of Applied Science, 2024)
A strong and light body shape is an important factor in the Energy Saving Car Contest. The shape and material of the body used affects the speed of the car. Composite materials are often chosen as material for making Energy Saving Car Contest bodies, because they are strong, light and have a fiber structure that binds each other. So this research aims to determine the effect of variations in catalyst composition on composite materials using fiberglass, woven roving and resin to obtain optimum composite results. Variations in the composition of the catalyst used are 1; 1.5; 2 and 2.5 %. Based on the results of the tests that have been carried out, tensile test results were obtained with the highest results, namely for 2.5% catalyst composition variation of 72.23 MPa and the lowest value was 27.1 MPa for a 1% catalyst composition. The greater the catalyst composition causes the tensile strength value to increase. The highest max force and modulus of elasticity test results were obtained with a 2% variation in catalyst composition, namely 7217 MPa and 16.30 MPa. Meanwhile, the highest impact test results obtained were 10.65 Joules with a catalyst variation of 1.5%..